Health Seeking Behaviour Among Elderly People of Bharatpur Municipality of Chitwan, Nepal - Baral, Rojina; Sapkota, Pramila (Journal of College of Medical Sciences-Nepal, 2018)
ABSTRACT Background: Individuals have different opinion regarding willingness to seek help from health care services. Some go readily for treatment, others only when in great pain and in advance state of ill health. This is especially true for people with advance age who have to face many physiological changes which act as a barrier to seek immediate help in health care setting. Thus, a study was conducted to analyse the health seeking behaviour among elderly. Materials and Methods: A cross-sectional analytical study was conducted among 104 elderly aged 60 years and above. Non- probability convenience sampling technique was used to collect the data. Data was collected by interviewing the elderly at their residence. The data gathered was analyzed using both descriptive and inferential statistics in SPSS software. Results: Assessment of the health status of elderly people revealed that, majority of the participant’s 86.5% were suffering from chronic health problem, among them 37.8% suffered from hypertension 11.1% suffered from diabetic mellitus. Whereas, assessment of the practice of health seeking behaviour among elderly stated that all the participant’s 100% were seeking help for health problem in which 83.7% seek help from modern medication and still 16.3% seek help from alternative medication. Also, the health seeking behavior was found to be statistically significant with health problem (p=0.002), ethnicity (0.007) and religion (p=0.007) respectively. Conclusions: Elderly are aware of seeking help from the health care center, but still elderly believe in alternative medication rather than modern medication which may be an alarming truth in the health care setting. Keywords: alternative medication; elderly; health seeking behaviour; modern medication.